Variation of Nd and Vfb for different compositions of CdSexTe1−x thin films by pulse plating technique - SAAMINATHAN, V; MURALI, K (2006)
CdSexTe1-x thin films with 0 < x < 1 have been pulse electrodeposited oil titanium (Ti), nickel (Ni) and stainless-steel (SS) substrates with different duty cycles. The size of the particles could be controlled by the pulse parameters. The deposition was carried out at room temperature for I It under potentiostatic mode with CdSO4, SeO2, TeO2, and H2SO4 as precursors. As-deposited and annealed films coated on Ti, Ni and SS were characterized by X-ray diffraction technique and SEM, and their electrical properties were studied. The as-deposited films exhibited a cubic structure; those after heat treatment at 500 degrees C in air exhibited a hexagonal structure. Variation of donor concentration and the flat band potential for different values of 'x' and duty cycles were studied for CdSexTe1-x thin films. The semiconductor parameters for all compositions coated on Ti, Ni and SS were estimated. It showed good agreement with the earlier reports. (c) 2005 Elsevier B.V. All rights reserved.